PEMBERDAYAAN MASYARAKAT DESA DALAM MENINGKATKAN LITERASI DIGITAL DAN KUALITAS HIDUP SECARA BERKELANJUTAN DI DESA SEJAHTERA. KEC. BULANGO SELATAN - Adnan Malaha; Ikram Mohammad; Starla Ramadani (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This community service program aims to improve digital literacy and the quality of life of the community in Sejahtera Village. South Bulango District, Bone Bolango Regency, through community-based empowerment. The methods used involve a participatory approach, digital literacy training, and mentoring of digital-based micro-enterprises. The results show an increase in community understanding of digital technology, the implementation of digital applications in micro-enterprises, and an increase in the quality of life socio-economically. This program contributes to the sustainability of village development through the integration of technology and community empowerment.